DEVELOPMENT OF A SYSTEM TRANSFORMATION OF NEW STUDENT ADMISSION SERVICES AND VALUE MANAGEMENT - Widi Astuti; Fajar Sarasati (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
Service activities at Tegal Dinamika Vocational School still use a manual system which has a high risk of data being lost and the authenticity of its value is doubtful. Based on these conditions, it is necessary to create a web-based grade processing information system to help convey information on student grades and attendance, as well as online registration data. The aim of this research is to provide a breakthrough in the transformation of services at Vocational School Dinamika Tegal in terms of registering new students, conveying information on exam results and attendance recaps to students and parents, which can be accessed online via the website, so that all users, even people with physical limitations, can access the website. that easily. The research method for web design uses the SDLC waterfall method. Apart from that, to determine website performance, researchers conducted sample usability testing to find out whether the website was user friendly. The results of this research with the creation of this application, the process of conveying value information from teachers to students has become more effective and efficient, this evidence can be seen from the distribution of questionnaires in the school environment which shows that 97% agree with this research, increasing the success of data processing and making it easier for the administrative side to be more organized and no more data errors. The uniqueness of this research focuses on more disability-friendly web design and user experiences that are accessible to all individuals including those with disabilities. The conclusion of this research is that the website is able to manage grade data and student attendance recaps that have been input by the teacher, making it easier for prospective new students to obtain registration information and register online and can be accessed anywhere and at any time through the system